Whistle-Blowing from the Perspective of General Strain Theory. Issue 2 (1st February 2019) - Kölbel, Ralf; Herold, Nico
ABSTRACT: Authorities in many countries rely on whistle-blowing systems to boost control of organizational deviance. It can hardly be answered whether this practice is legitimate and efficient without knowing the patterns of whistle-blower behavior. So far, little is known about the development process as an interaction of specific individual, organizational, and situational conditions that spawns especially external reports. This article reconstructs such typical progressions based on interviews with whistle-blowers in Germany and from the perspective of the General Strain Theory. It turns out that external whistle-blowing is often the result of an escalating conflict that can be interpreted as a very personal experience of strain.